Omega-3 polyunsaturated fatty acids and/or vitamin D in autism spectrum disorders: a systematic review - Jiang, Yuwei; Dang, Wenjun; Nie, Hong; Kong, Xiangying; Jiang, Zhimei; Guo, Jin (Frontiers in Psychiatry, 2023)
Abstract: This systematic review aims to offer an updated understanding of the relationship between omega-3 supplementation and/or vitamin D and autism spectrum disorders (ASD). The databases PubMed, Cochrane Library, Web of Science, EMBASE, CINAHL, Vip, CNKI, Wanfang, China Biomedical Database databases were searched using keywords, and relevant literature was hand-searched. Papers (n = 1151) were systematically screened and deemed eligible since 2002. Twenty clinical controlled studies were included in the final review. The findings were analysed for intervention effects focusing on the core symptoms of ASD, included social functioning, behavioural functioning, speech function and biomarkers changes. The review found that the effects of omega-3 supplementation on ASD were too weak to conclude that core symptoms were alleviated. Vitamin D supplementation improved core symptoms, particularly behavioural functioning, however, the results of the literatures included in this study were slightly mixed, we cannot directly conclude that vitamin D supplementation has a beneficial effect on a specific symptom of ASD, but the overall conclusion is that vitamin D supplementation has a positive effect on behavioural functioning in ASD. Omega-3 and vitamin D combination supplementation has a good combined effect on social and behavioural outcomes in patients with ASD.